The Pattern of Hematological and Biochemical Parameters in Dengue Fever among Patients Presenting to HIT Hospital, Taxila Cantt: Hematological and Biochemical Parameters in Dengue Fever - Umar, Sana; Javed, Ayesha; Aslam, Ummara; Abbas, Syed Hassan Burair; Yasmin, Raheela; Rauf, Manal; Javed, Ambreen; Sadiq, Sarah; Rauf, Shahid (Pakistan Journal of Health Sciences, 2025)
Dengue fever affects over 600 million people globally each year, with its burden increasing eightfold in the past 15 years. It is endemic in 129 nations. Objective: To identify the pattern of hematological and biochemical parameters in patients at HIT Hospital, Taxila, and examine their correlation. Methods: This retrospective cross-sectional study analyzed data from 118 patients with positive serology reported between August and November 2022. Parameters studied included hemoglobin, hematocrit, platelets, leucocyte count, and plasma Alanine transaminase (ALT) levels. Results: Among 118 patients, 77 were male, and 41 were female. Patients under 18 years comprised 8.5%, those aged 18–49 years constituted 61.0%, and those aged 50+ accounted for 30.5%. Severe dengue cases showed significantly reduced platelet counts across all age groups (p < 0.05). In mild dengue, 3 of 17 patients had normal ALT levels, while 11 showed abnormal levels. In moderate cases, 27 of 87 had normal ALT levels, while 60 exhibited elevated levels. Severe cases showed elevated ALT levels in 16 of 17 patients. Conclusions: Males and individuals aged 18–49 are more vulnerable to dengue and should take extra precautions. Elevated liver transaminases, leucopenia, and thrombocytopenia indicate a high likelihood of dengue infection, aiding diagnosis and treatment planning. Awareness campaigns must be expanded to larger populations, including literate individuals, to prevent the disease effectively.